Whist; or, Bumblepuppy? Thirteen Lectures Addressed to Children - Hewby, John Petch, 1835-1896 (Salt Lake City, UT : Project Gutenberg, 2017)
"Whist; or, Bumblepuppy? Thirteen Lectures Addressed to Children" by John Petch Hewby is a guide on the card game Whist, likely written in the late 19th century. The text presents a series of lectures designed for children to understand strategies and etiquette associated with the game, while also addressing the more casual and arguably chaotic alternative known as Bumblepuppy. The book aims to refine the skills of its young readers, distinguishing effective techniques from ineffective ones in the context of playing Whist. The opening of the work sets the stage for a detailed exploration of Whist and Bumblepuppy, beginning with an overview of the significance of choosing one game over the other. The author emphasizes the necessity of understanding the game's principles for one$1 (Bs own comfort as well as that of fellow players. It humorously critiques the confusion between the two games, outlining the implications of poor play and the importance of adhering to the true strategies of Whist. By defining Bumblepuppy as subpar play, Hewby encourages serious engagement with the game, hinting at the potential for improvement and enjoyment through diligent practice and sound reasoning. (This is an automatically generated summary.)s
Release date is 2017-02-08
E-text prepared by Emmy, MFR, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images digitized by the Google Books Library Project (http://books.google.com and generously made available by Internet Archive (https://archive.org)
Keywords: Whist